2003
DOI: 10.1164/rccm.200209-1097oc
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis Susceptibility and Resistance HLA-DQB1 Alleles in African Americans

Abstract: Sarcoidosis, in the United States, more commonly and severely affects African Americans. HLA associations with sarcoidosis have been reported, but most studies used case-control designs, which may produce biased results because of population stratification. We examined transmission of HLA-DQB1 alleles in 225 African American families with at least one offspring with sarcoidosis. Of five low-resolution HLA-DQB1 alleles, *02 and *06 showed significant deviation in transmission patterns to affected offspring. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 48 publications
3
75
1
6
Order By: Relevance
“…We thought this dense marker coverage of the MHC was warranted given the strong linkage to sarcoidosis found in German Caucasians and the multitude of reported HLA associations with sarcoidosis including an association we previously reported between HLA-DQB1 and sarcoidosis susceptibility in a separate African-American sample. 16 We found no evidence for linkage of sarcoidosis susceptibility to the MHC region of chromosome 6p in our SAGA study population. The SAGA study did have potential agreements with the previously reported scan by Schurmann et al 14 on chromosomes 1p and 9q.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We thought this dense marker coverage of the MHC was warranted given the strong linkage to sarcoidosis found in German Caucasians and the multitude of reported HLA associations with sarcoidosis including an association we previously reported between HLA-DQB1 and sarcoidosis susceptibility in a separate African-American sample. 16 We found no evidence for linkage of sarcoidosis susceptibility to the MHC region of chromosome 6p in our SAGA study population. The SAGA study did have potential agreements with the previously reported scan by Schurmann et al 14 on chromosomes 1p and 9q.…”
Section: Discussioncontrasting
confidence: 62%
“…On the basis of 225 microsatellite markers tested in 63 German families (Caucasians) with affected sib pairs, linkage at the major histocompatibility complex (MHC) on chromosome 6p was found with additional suggested linkage to markers on chromosome 1, 3, 9 and X. 14 Several candidate genes from the MHC region have been investigated [15][16][17] with the DRB1 gene most consistently identified as a risk factor for sarcoidosis. [18][19][20] Replicating linkage findings in additional samples is key to unraveling the genetics of complex diseases, such as sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Much genetic research to date has focused on the roles of genes governing the molecules necessary for antigen-specific T-cell stimulation. In this regard, numerous investigators have described disease associations with HLA polymorphisms, especially those coding for Class II molecules [3,4]. Predictably, analysis of T-cell receptor variants has also revealed patterns associated with disease susceptibility or phenotype [46].…”
Section: Gene-environment Interactions In Sarcoidosis Evidence For Mamentioning
confidence: 99%
“…The first study to systematically examine gene-environment interactions employed familybased association analysis to identify HLA-DQB1 susceptibility alleles in 704 individuals from 225 African-American families [3]. Unclear consanguity, suspected by finding non-Mendelian segregation for a panel of unlinked genomic markers, resulted in exclusion of 8% of the families.…”
Section: Evidence For Interactionmentioning
confidence: 99%
See 1 more Smart Citation